CML/RAGE Signal Bridges a Common Pathogenesis Between Atherosclerosis and Non-alcoholic Fatty Liver - Pang, Qiwen; Sun, Zhen; Shao, Chen; Cai, Honghua; Bao, Zhengyang; Wang, Lin; Li, Lihua; Jing, Lele; Zhang, Lili; Wang, Zhongqun (Frontiers in Medicine, 2020)
Non-alcoholic fatty liver disease (NAFLD) has become a common chronic disease in the world. NAFLD is not only a simple intrahepatic lesion, but also affects the occurrence of a variety of extrahepatic complications. In particular, cardiovascular complications are particularly serious, which is the main cause of death in patients with nonalcoholic fatty liver disease. To study the association betweenNAFLD and AS. It may be a new way to improve the quality of life of patients with nonalcoholic fatty liver disease. As we all known, inflammatory response plays an important role in the occurrence and development of NAFLD and AS. In this study, we found that the accumulation of N ε - carboxymethyllysine(CML) in the liver leads to hepatic steatosis. CML can induce the expression of interleukin (IL)-1β,interleukin (IL)-6, tumor necrosis factor (TNF)-α,C-reactionprotein(CRP) by binding with advanced glycosylation end-product receptor (RAGE) and accelerate the development of atherosclerosis. After silencing RAGE expression, the expression of pro-inflammatory cytokines was inhibited and liver vascular pathological changes were relieved. In conclusion, CML / RAGE signal promotes the progression of non-alcoholic fatty liver disease and atherosclerosis. We hope to provide new ideas for the study of liver vascular dialogue in multi organ communication.